AN ETHNOGRAPHY STUDY OF FARMERS’ SOCIOEDUPRENEURSHIP IN TAPUT NORTH SUMATERA INDONESIA - ., Luhut Mawardi (Universitas Asahan, 2024)
Abstract The study figures out the context of the socio cultural of the farmers in Tapanuli Utara (TAPUT), North Sumatera Indonesia. As the background of the study was the condition of the farmers looked like worry people while finding and waiting for chemical fertilizer (CF) imported from abroad hopelessly. Why it happened was because of chemical fertilizer as the basic needs for rice and other plantations suddenly lost from the marketing of all over Indonesia, which is in fact, the farmers used to take it as their needs to fertilize their plants at the farm or field and even, though it is at the high price cost, the farmers ought to get it for their plants by owing some money from the bank or money creditor (for the poor ones). The people make it as a need to have, as a means of quantifying and qualifying the result of farming. In such a worry condition, the researchers think and find the best solution for the society by presenting a team to educate the society on the theme of enterpreneurship with a target ‘Self-producing Liquid Organic Fertilizer (LOF) for self-use, it is named Socioedupreneurship. In this case, the role of the researchers besides to conduct a research, and also to educate and to give service in worship of christian so they can improve their belief in God. The problem of the study was; Why the society of Taput North Sumatera cannot find chemical fertilizer (CF) as the main fertilizer they used to use which makes them confused and disappointed?, and how can they overcome such a problem massively?. The focus of the research was that rice plantation can be quantifying and qualifying the harvest by using Liquid Organic Fertilizer (LOF) instead of Chemical Fertilizer (CF), and this is the first time happened in TAPUT since the last 7 decades. It is reasonable to mention that the research belongs to ethnography study because of the phenomenon stated above. The research method used was ethnomethodology for the purpose of indepht data gathering from the informants, besides indepth socio aproach interaction which includes in the method. Since the research used ethnomethodology to find the data, thus the findings of the research are transcripted in descriptive qualitative, of which data resources were gathered in verbal and nonverbal interaction from the informant or the subject of the study. As the result, 1) 98 % of the farmers used to take CF as the basic or main fertilizer for farming and the 2% was no response, they cannot find CF as the basic needs to fertilize the plants, and it has been done for 7 decades. 2) From the reasoning at the data display proved that, 90 % of the informants said that the lost of CF in Indonesia marketing is because of the world war between Russian and Croatian which impacts directly to the world business especially CF importing. 3) as the novelty of the research, there is a best solution from the researchers for the farmers to overcome such a hidden/latent problem by educating the society of TAPUT which is majorly are farmers conducting enterpreneurship of Liquid Organic Fertilizer (LOF), to produce LOF using some easy getting organic materials that the elements can fertilize the land and make the plants grow up well and can multiply the harvest either the quantity or quality, as well. Finally, at the period of post harvesting, the society of TAPUT North Sumatera Indonesia 98 % said that they are happy or better to lose the CF and to have LOF instead, as the own or self creation of the farmers. In conclusion, from the worriness and disappointed of the society at the first experience loosing the CF as the basic needs of rice fields and other plantations in TAPUT North Sumatera, finally they are happy and satisfied after having the educative solution from the researchers. The reasonings of the happiness are: 1) The impact of the research can minimize the budget of fertilizer from IDR 1.800.00.000,- (price of CF) decreased to IDR 100.000,- (price of LOF) per hectare (saved up to IDR 1.000.000,-). 2) The quality and the quantity of the harvest as well, are improved simultanously. 3) the nutrient of the land or farm is kept clinical from the heap of the former chemical fertilizer use. Keywords: Ethnography study, Socioedupreneurship, Liquid Organic Fertilizer (LOF), Chemical Fertilizer (CF)